The determination of the intersection of projective plane P2 (K) curves based on the bezout's theorem - Santika, 1990- , author; Nor Aini Aris, supervisor; Normah Maan, supervisor; Fakulti Sains (2015)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2015